Resilience, Cultural Beliefs, and Practices That Mitigate Suicide Risk Among African American Women Veterans - Brooke A. Dorsey Holliman; Lindsey L. Monteith; Elizabeth G. Spitzer; Lisa A. Brenner (SAGE Open, 2018)
To our knowledge, no studies have examined protective factors for suicide among African American women Veterans. We conducted a qualitative study to identify and describe cultural beliefs and practices that mitigate suicide risk among African American women Veterans. Our sample included 16 African American women Veterans ( M age = 53.3) eligible to receive Veterans Health Administration care. The following three themes emerged as being protective against suicide: (a) resilience, (b) social support, and (c) religion. Women described developing resilience from exposure to adversity. Social support primarily entailed informal assistance from family and friends. Finally, religion comprised three subthemes: faith in God, personal practices, and religious beliefs. Results underscore the importance of specific cultural beliefs and practices as being protective against suicide among African American women Veterans.